IoT System Design for Money Drawer Security Using Keypad and Selenoid Lock with Telegram Notification - Nadza Irawan, Reza (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The security of cash storage remains a crucial issue, especially for households and small-scale businesses that frequently handle cash transactions. Conventional storage methods often lack advanced security features, making them vulnerable to unauthorised access. To address this problem, this study focuses on the design and development of an Internet of Things (IoT)-based security system specifically for a cash drawer. The system employs a keypad as the primary input device for authentication, combined with a solenoid lock that functions as the locking mechanism. In addition, users receive real-time notifications through the Telegram application whenever the drawer is opened or closed, thereby enhancing user awareness and security monitoring. The hardware architecture integrates the NodeMCU ESP8266 microcontroller, which serves as both the central processing unit and the module for internet connectivity. System testing was carried out under several scenarios, such as successful PIN entry, incorrect PIN input, and simulated break-in attempts. The results demonstrate that the proposed IoT-based system is capable of increasing the security level of cash storage while providing convenience through real-time monitoring.